2022
DOI: 10.3389/fphys.2022.995575
|View full text |Cite
|
Sign up to set email alerts
|

Validity of three smartwatches in estimating energy expenditure during outdoor walking and running

Abstract: Commercially wrist-worn devices often present inaccurate estimations of energy expenditure (EE), with large between-device differences. We aimed to assess the validity of the Apple Watch Series 6 (AW), Garmin FENIX 6 (GF) and Huawei Watch GT 2e (HW) in estimating EE during outdoor walking and running. Twenty young normal-weight Chinese adults concurrently wore three index devices randomly positioned at both wrists during walking at 6 km/h and running at 10 km/h for 2 km on a 400- meter track. As a criterion, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Therefore, we are confident of the reliability of the energy expenditure records obtained using the Apple Watch in this study. [5][6][7][8][9][10][11][12] Our research indicated that liposuction has the highest energy output among plastic surgeons. This physical activity requires covering 5.7 km in 31 minutes, representing an impressive and considerable effortfar exceeding any other type of operation-to obtain 4407 cm 3 of fat at a heart rate of 90 beats per minute.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, we are confident of the reliability of the energy expenditure records obtained using the Apple Watch in this study. [5][6][7][8][9][10][11][12] Our research indicated that liposuction has the highest energy output among plastic surgeons. This physical activity requires covering 5.7 km in 31 minutes, representing an impressive and considerable effortfar exceeding any other type of operation-to obtain 4407 cm 3 of fat at a heart rate of 90 beats per minute.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, we are confident of the reliability of the energy expenditure records obtained using the Apple Watch in this study. 5–12…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 16 , 32 However, these wearable devices exhibit errors ranging from 27% to 93% when evaluated using new subjects. 2 , 33 Furthermore, the overall correlation with indirect calorimetry was observed to be 0.34 for all monitors. 25 To improve prediction accuracy, researchers have studied new approaches involving machine learning (ML) and deep learning algorithms to develop regression models for monitoring walking EE.…”
Section: Introductionmentioning
confidence: 84%
“…Aligning with findings from other smartwatch research on TDAEE [38,[39][40][41][42], our results reveal that while the GT2 demonstrates moderate validity compared to the Actigraph, its in TDAEE measurements is still not ideal as shown by a high level of errors against Actigraph (MAPE>30%). Le et al [43] previously analyzed the GT2's EE accuracy against the Cosmed K5 in outdoor scenarios, reporting ICCs of .76 and .68, and MAPEs of 9.9% and 11.9% in walking (6 km/h, 2 km) and running (10 km/h, 2 km) scenarios, respectively. These findings generally agree with our results, underscoring the GT2's relative accuracy in energy expenditure measurement.…”
Section: Discussionmentioning
confidence: 99%
“…While the accuracy of smartwatches has been explored in previous research studies, research specifically focusing on their performance across different age groups in a free-living environment remains scarce, particularly within the Chinese population. The Huawei smartwatch ranks second in global sales in Q2 2023 and holds a high market share of 39% in China [57], but received limited empirical research attention on its accuracy [22,43], especially with regard to measurements of energy expenditure and sleep duration [38,53,58]. Considering its significant market prominence, it is crucial to rigorously assess the accuracy of the Huawei smartwatch in measuring health-related indices to ensure its validity for users' health monitoring and lifestyle management.…”
Section: Original Manuscriptmentioning
confidence: 99%